1983
DOI: 10.1007/bf00294992
|View full text |Cite
|
Sign up to set email alerts
|

Human hair follicles and cultured hair follicle keratinocytes as indicators for individual differences in carcinogen metabolism

Abstract: Benzo(a)pyrene (BP)-metabolism in freshly isolated human hair follicles, cultured hair follicle keratinocytes and cells cultured from human bronchial epithelium was analysed by high performance liquid chromatography. All three types of tissues resulted in quantitatively comparable amounts of the most important organic solvent-soluble metabolites: 9,10-dihydrodiol-BP, 7,8-dihydrodiol-BP, quinones, and phenols. Besides these metabolites two early eluting compounds were detected: one possibly is BP-3-yl-hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It has been shown that human hair follicles metabolize benzo[a]pyrene m a similar way to human bronchial epithelial cells (Hukkelhoven, Dijkstra & Vermorken, 1983). Therefore hair bulbs are a very suitable tissue to investigate whether the AHH-controlling gene is of significance in producing human cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that human hair follicles metabolize benzo[a]pyrene m a similar way to human bronchial epithelial cells (Hukkelhoven, Dijkstra & Vermorken, 1983). Therefore hair bulbs are a very suitable tissue to investigate whether the AHH-controlling gene is of significance in producing human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…H.Merk et al liquid chromatography (Vermorken et al, I979a,b;Hukkelhoven, Dijkstra & Vermorken, 1983). However, in cultured human hair follicles no AHH inducibility was detected (Hukkelhoven et al, 1981a).…”
mentioning
confidence: 99%